Discovery of prostamide F2α and its role in inflammatory pain and dorsal horn nociceptive neuron hyperexcitability. - Luisa Gatta; Fabiana Piscitelli; Catia Giordano; Serena Boccella; Aron Lichtman; Sabatino Maione; Vincenzo Di Marzo (PLoS ONE, 2012)
It was suggested that endocannabinoids are metabolized by cyclooxygenase (COX)-2 in the spinal cord of rats with kaolin/λ-carrageenan-induced knee inflammation, and that this mechanism contributes to the analgesic effects of COX-2 inhibitors in this experimental model. We report the development of a specific method for the identification of endocannabinoid COX-2 metabolites, its application to measure the levels of these compounds in tissues, and the finding of prostamide F(2α) (PMF(2α)) in mice with knee inflammation. Whereas the levels of spinal endocannabinoids were not significantly altered by kaolin/λ-carrageenan-induced knee inflammation, those of the COX-2 metabolite of AEA, PMF(2α), were strongly elevated. The formation of PMF(2α) was reduced by indomethacin (a non-selective COX inhibitor), NS-398 (a selective COX-2 inhibitor) and SC-560 (a selective COX-1 inhibitor). In healthy mice, spinal application of PMF(2α) increased the firing of nociceptive (NS) neurons, and correspondingly reduced the threshold of paw withdrawal latency (PWL). These effects were attenuated by the PMF(2α) receptor antagonist AGN211336, but not by the FP receptor antagonist AL8810. Also prostaglandin F(2α) increased NS neuron firing and reduced the threshold of PWL in healthy mice, and these effects were antagonized by AL8810, and not by AGN211336. In mice with kaolin/λ-carrageenan-induced knee inflammation, AGN211336, but not AL8810, reduced the inflammation-induced NS neuron firing and reduction of PWL. These findings suggest that inflammation-induced, and prostanoid-mediated, enhancement of dorsal horn NS neuron firing stimulates the production of spinal PMF(2α), which in turn contributes to further NS neuron firing and pain transmission by activating specific receptors.